Unveiling pathways: exploring chronological and maturational biases in a Spanish professional soccer academy - Peñín-Grandes, Saúl; Mesonero-García, Silvia; Huertas Olmedo, Florentino; Ginés Cabeza, Honorato Jose; Ballester Lengua, Rafael (Frontiers in Sports and Active Living, 2025)
This brief research report aimed to analyze the prevalence of asymmetries in players' date of birth, the influence of relative age affects (RAEs) and maturation on players' participation, and the potential maturity biases in performance indicators in a Spanish professional male soccer academy. Maturity status was determined as the percentage of predicted adult height (%PAH). RAEs are strongly represented in the sample as 77% of players were born in the first semester of the year. Relatively older players do not appear to receive significantly more playing minutes, while more mature players showed a higher percentage of playing time in U13 and U14, with no differences in U15 and U16. In other performance indicators, more mature players do not have an advantage when it comes to being considered “promising players”, training and competing with higher chronological age groups and being selected by state teams. Finally, individual maturity level within the team does not appear to be relevant to the club's proposal to continue in the academy. Our results show a strong overrepresentation of players born in the first semester of the year, indicating the presence of RAEs. However, this bias does not translate into significant differences in competitive performance, such as playing time. Conversely, individual maturity status demonstrates a transient effect on playing time in younger age groups (U13 and U14). These findings underscore the importance of understanding the interplay between RAEs and maturity biases in talent identification and development in the highly competitive framework of a professional soccer academy.